SENYAPAN DAN KILIR LIDAH PADA KOMEDIAN AKIBAT PENYIMPANAN MEMORI DALAM PREFRONTAL CORTEX - Luffiati Gina Puspita; Khalid Abdullah Harras; Jatmika Nurhadi (Universitas Muhammadiyah Surakarta, 2022)
This study aims to discuss pauses and slips of the tongue in comedian and relation to memorystorage in the prefrontal cortex on the utterance of Indonesian comedian Dustin Tiffani in“Mencoba Mengerti'' on YouTube channel Majelis Lucu Indonesia (MLI). This research is adescriptive qualitative method through descriptions systematically based on the facts of thephenomenon. The data techniques used are listening, note-taking, and documentation techniqueswith stages: (1) listening and analyzing Dustin Tiffani’s videos which was published on Youtube;(2) transcribing as card data in Dustin Tiffani’s videos; (3) classifying the data based on pausesand slips of the tongue theory, and (4) describing the results research on findings and discussion.The study found that disturbances in speaking were in the form of pauses are: (1) filled silences;(2) silent silences, and; (3) combined silences, whereas in the slips of the tongue found in the form of: (1) errors in the semantic selection; (2) mixed words (blends); (3) errors in the assembly, and; (4) errors in syllables. The phenomenons are related to the function of the prefrontal cortex as a memory storage area due to head trauma that has been suffered and affects Dustin Tiffani's speech.Keywords: Dustin Tiffani, pause, slips of the tongue, psycholinguistics, prefrontal cortex